(RETRACTED) The Reconstruction of Women's Position and Role through Irigaray's Ethics of Sexual Differences in the Culture of Manggarai, Flores, East Nusa Tenggara - Priskardus Hermanto Candra; Asih Zunaidah; Frederik Masri Gasa (Sawwa: Jurnal Studi Gender, 2020)
Reason for Retraction (March 26th, 2021):This paper is retracted by the editors due to publication ethics misconducted by authors (simultaneous publication in another journal). According to the author's statement, the manuscript was published in another journal under the title â€œRelasi Perempuan dan Laki-laki menurut Luce Irigaray.â€Â DOI:Â 10.15408/harkat.v16i2.16887